Seorang Wanita Mengalami Aspirasi Barium Dengan Komplikasi Pneumonia : [Barium Aspiration Complicating Pneumonia in a Woman: A Case Report] - Isnin Anang Marhana; Adhari Ajipurnomo (Faculty of Medicine Universitas Airlangga, 2019)
Background. Barium aspiration is one of rare major complication of esophagography. Aspiration pneumonia occurs about 40% without clinical symptom and can cause 30% of dead. Case. A female 62 years old choked a mount of barium when swallowing barium liquid in esophagography procedure. There was ronkhi on lower left haemithorax and granuler pattern on left paracardial impressed the rest of barium in chest x-ray photo. Patient suffered symptom of infection in eight days evaluation with infiltrate and rest of barium from chest x-ray photo. Microbiology examination of bronchus lavage founded pathogen microbe Burcholderia Gladioli and Pseudomonas and containing 1,22 mg/L of barium. Discussion. Barium aspiration can occur in esophagography procedure in extreme age. Chest x-ray and Computed Tomography can be used as primer tool to diagnose and evaluate barium aspiration which imaging hiperdens pattern due to barium with high atomic number (56). Prognosis of aspiration barium can be affected by the quantity and density of barium liquid which is choked and comorbid factor in patient. Barium aspiration mixed with secrete of oropharing which containing colony of pathogen can cause penumonia as disease complication. There is still no guideline for barium aspiration management, but bronchoscopy is recommended by many clinician. Conclusion. Pneumonia occur when aspiration barium mixed with secrete oropharing which containing colony of pathogen. Chest x-ray and CT scan can be used as tool to diagnose barium aspiration. Bronchoscopy is recommended to diagnose and to manage barium aspiration. When pneumonia is suspicious, antibiotic with anaerob activity is recommended given.